Identification of Transcriptional and Receptor Networks That Control Root Responses to Ethylene. Issue 3 (19th December 2017) - Harkey, Alexandria F.; Watkins, Justin M.; Olex, Amy L.; DiNapoli, Kathleen T.; Lewis, Daniel R.; Fetrow, Jacquelyn S.; Binder, Brad M.; Muday, Gloria K.
Abstract : The kinetics of changes in the ethylene transcriptome in light-grown roots combined with mutant analyses reveal a central role of the ETR1 receptor and a limited role of EIN3 in root development. Abstract: Transcriptomic analyses with high temporal resolution provide substantial new insight into hormonal response networks. This study identified the kinetics of genome-wide transcript abundance changes in response to elevated levels of the plant hormone ethylene in roots from light-grown Arabidopsis ( Arabidopsis thaliana ) seedlings, which were overlaid on time-matched developmental changes. Functional annotation of clusters of transcripts with similar temporal patterns revealed rapidly induced clusters with known ethylene function and more slowly regulated clusters with novel predicted functions linked to root development. In contrast to studies with dark-grown seedlings, where the canonical ethylene response transcription factor, EIN3, is central to ethylene-mediated development, the roots of ein3 and eil1 single and double mutants still respond to ethylene in light-grown seedlings. Additionally, a subset of these clusters of ethylene-responsive transcripts were enriched in targets of EIN3 and ERFs. These results are consistent with EIN3-independent developmental and transcriptional changes in light-grown roots. Examination of single and multiple gain-of-function and loss-of-function receptor mutants revealed that, of the five ethylene receptors, ETR1 controls lateral root and root hair initiation and elongation and the synthesis of other receptors. These results provide new insight into the transcriptional and developmental responses to ethylene in light-grown seedlings.